Reproduction of Knowledge for Power: Critical Discourse Analysis of Scientific Articles and Speeches of Megeawati - Febi Putri Utami; Rustono Rustono; Bernadus Wahyudi Joko Santoso (Edumaspul: Jurnal Pendidikan, 2023)
The inauguration of Megawati Soekarnoputri as an honorary professor at the Defense University of the Republic of Indonesia became a topic of conversation among the public because this was the first time this had happened in Indonesia. Megawati wrote a scientific work entitled "President Megawati's Leadership in the Era of Multidimensional Crisis, 2001-2004" and gave a speech at her inauguration as Non-Permanent Professor. The two texts discuss the problems that occurred during the era of Megawati's leadership, policies to overcome problems, and the emergence of a model of "strategic leadership based on Pancasila". The leadership discourse formed by Megawati is interesting to discuss considering Megawati's position, who is the general chair of the Indonesian Democratic Party of Struggle (PDI-P), as well as chair of the Steering Committee of the Pancasila Ideology Development Agency (BPIP) and the National Research and Innovation Agency (BRIN). This research uses a qualitative approach with a critical paradigm. The research method uses critical discourse analysis coined by Fairclough, where Megawati's scientific work and inauguration speech are reviewed from the perspective of text, discursive practice and social practice. Fuchs, Habermas, and Foucault's views on knowledge and power are used to help uncover discursive practices and their impact on social practice. Based on the results of the analysis, Megawati is building a positive image as an influential strategic leader to this day. The leadership model he initiated focuses on the leader's ability to influence others and pay attention to the role of the people in decision making. The knowledge that is built is Pancasila, which is the basis for every social activity which actually reduces its values to a controlled knowledge system. The impact that arises is that the state's control over individuals is increasingly tight, down to the cognitive level. When drawn to the momentum of the 2024 general election, leadership discourse was used to help Megawati and her group return to power.